Gemcitabine and Docetaxel Compared With Observation, Radiation, or Other Chemotherapy Regimens as Adjuvant Treatment for Stage I-to-IV Uterine Leiomyosarcoma. Issue 3 (1st March 2016) - Roque, Dario R.; Taylor, Kristin N.; Palisoul, Marguerite; Wysham, Weiya Z.; Milam, Brian; Robison, Katina; Gehrig, Paola A.; Raker, Christina; Kim, Kenneth H.
Abstract : Objectives: We aimed to compare progression-free survival (PFS) and overall survival (OS) among patients with stage I-to-IV uterine leiomyosarcoma (uLMS) who received adjuvant gemcitabine-docetaxel, were observed, received radiation only, or were treated with a chemotherapy regimen other than gemcitabine-docetaxel. Methods/Materials: This is a retrospective cohort study of 128 women with uLMS. Data included age, body mass index, race, stage, mitotic count, residual disease, adjuvant treatment, PFS, and OS. Variables were compared by Fisher exact or Wilcoxon rank-sum tests. Time to progression or death was plotted using Kaplan-Meier curves. Cox proportional hazards regression was used to estimate hazard ratios for progression or death by patient and tumor characteristics. Results: Fifty-six (44%) women received adjuvant chemotherapy, 41 (32%) received adjuvant radiation, and 31 (24%) were observed. Of those receiving chemotherapy, 30 received gemcitabine-docetaxel, and 26 received other chemotherapy. Disease stage for the chemotherapy groups was evenly distributed. In the radiation group, 80% of patients had early-stage disease. Age, body mass index, and residual disease were similar between the groups. Mitotic count was uniformly 10 or greater only in the gemcitabine-docetaxel group. Age, stage, and residual disease were associated with worst PFS and OS. After adjusting for these variables, there was no difference in PFS or OS between gemcitabine-docetaxel and the other treatment groups. Conclusions: There was no difference in PFS or OS in women with uLMS treated with adjuvant gemcitabine-docetaxel versus those who were observed or received radiation only or a chemotherapy regimen other than gemcitabine-docetaxel. There is a need to identify novel therapies to treat this aggressive disease.